Immediate dental and skeletal influence of distractor position on surgically assisted rapid palatal expansion with or without pterygomaxillary disjunction. Issue 5 (May 2021) - Möhlhenrich, S.C.; Ernst, K.; Peters, F.; Kniha, K.; Chhatwani, S.; Prescher, A.; Danesh, G.; Hölzle, F.; Modabber, A.
Abstract: The outcome of surgically assisted rapid palatal expansion (SARPE) can be affected by pterygomaxillary disjunction (PMD) and the distractor position. In this study, SARPE was performed, with or without PMD, in 20 fresh cadaver heads. Transverse expansion was conducted twice using a bone-borne distractor in the anterior and posterior positions, resulting in four groups ( n = 10). Cone beam computed tomography scans were completed before and after SARPE to evaluate maxillary changes. A comparative anterior decrease and posterior increase in midpalatal opening resulted from SARPE with PMD combined with a posteriorly placed distractor. Significant differences in the internal transverse changes were found between the two SARPE techniques combined with an anterior distractor at the level of the premolars and molars for alveolar ridge width ( P = 0.040, P = 0.024), and at the level of the molars for the dental crown width ( P = 0.017) and corresponding tooth cusp width ( P = 0.018). In contrast, using a posteriorly placed distractor led to a significant difference for tooth cusp width only ( P = 0.050). No statistically significant differences were found between external transverse changes or between distractor positions. PMD is more important in achieving a more uniform and parallel transverse expansion pattern than the distractor position. However, a posterior distractor seems to intensify the effects of PMD.